Localized state effect and exciton dynamics for monolayer WS2 - Xu, Xuejun; Li, Lihui; Yang, Mingming; Guo, Qinglin; Wang, Ying; Li, Xiaoli; Zhuang, Xiujuan; Liang, Baolai (Optics express, 2021)
The two-dimensional transition metal dichalcogenides (TMDCs) have been considered as promising candidates for developing a new generation of optoelectronic devices. Accordingly, investigations of exciton dynamics are of great importance for understanding the physics and the performance of devices based on TMDCs. Herein, after exposure to ambient environment for six months, monolayer tungsten disulfide (WS2) shows formation of localized states. Photoluminescence (PL) and time-resolved PL (TRPL) spectra demonstrate that these localized states have significant impacts on the exciton dynamics, including energy states filling, thermal activation and redistribution, and the decay behavior of excitons. These observations not only enrich the understanding for localized states and correlated exciton dynamics of aged monolayer WS2, but also reveal a possible approach to modulate the optical properties of TMDCs via the aging process.The two-dimensional transition metal dichalcogenides (TMDCs) have been considered as promising candidates for developing a new generation of optoelectronic devices. Accordingly, investigations of exciton dynamics are of great importance for understanding the physics and the performance of devices based on TMDCs. Herein, after exposure to ambient environment for six months, monolayer tungsten disulfide (WS2) shows formation of localized states. Photoluminescence (PL) and time-resolved PL (TRPL) spectra demonstrate that these localized states have significant impacts on the exciton dynamics, including energy states filling, thermal activation and redistribution, and the decay behavior of excitons. These observations not only enrich the understanding for localized states and correlated exciton dynamics of aged monolayer WS2, but also reveal a possible approach to modulate the optical properties of TMDCs via the aging process.